Conserving species‐rich predator assemblages strengthens natural pest control in a climate warming context. (30th August 2016) - Drieu, Robin; Rusch, Adrien
Abstract: Recent evidence has shown that a consideration of multiple drivers is important if we want to understand how ecosystem functioning will respond to global change. In the present study, we used a substitutive approach to examine how two major components of global change, warming and predator diversity, affect the top‐down control of two phytophagous insect pests. Predator assemblages were created using a substitutive design to give three single‐species treatments (low diversity) and one three‐species treatment (high diversity) under two temperature treatments (current seasonal temperature and an increase of +3°C over current temperatures). The results obtained indicate a shift from substitutive to complementarity effects among predatory species with experimental warming. Experimental warming revealed complementarity between the predatory species in diverse assemblages because higher predation rates on both prey species were found in the high diversity treatment compared with what was expected based on low diversity treatments at the same temperature. Our analyses of prey selectivity provided evidence that resource‐niche partitioning is involved in the emergence of functional complementarity under warming. The present study highlights the importance of maintaining diverse predator assemblages if we want to increase natural pest control services in agroecosystems and reduce dependence on agrochemicals in a climate change context.